Labour clauses for sustainability? Colombian trade agreements exemplify potential and limits - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2018)
Modern free trade agreements increasingly seek to address environmental and social concerns. While the EU pursues a dialogue-led 'soft approach', the United States relies on threats of trade sanctions. Colombia offers an interesting example in this connection. It has agreements with the United States, Canada and the EU, which the respective parliaments declined to ratify until they included provisions to improve the situation of labour and the trade unions. Controversy over the fun-damental relationship between trade policy, sustainability and human rights has coloured the discussion in recent years. Experience already gathered with labour clauses permits conclusions to be drawn for the shape of future trade policy instruments, including those of the EU. The findings presented below confirm the importance of
Keywords: 320